Epigallocatechin gallate and coenzyme Q10 attenuate cisplatin‐induced hepatotoxicity in rats via targeting mitochondrial stress and apoptosis. Issue 4 (4th January 2021) - Fatima, Sabiha; Suhail, Nida; Alrashed, May; Wasi, Samina; Aljaser, Feda S.; AlSubki, Roua A.; Alsharidah, Ashwag S.; Banu, Naheed
Abstract: Despite the extensive use of cisplatin (CP) as a chemotherapeutic agent, its clinical use is often restricted by undesirable side effects, such as toxicity to normal tissues. The aim of this study was to probe the effect of a combinatorial treatment of low multiple doses of antioxidants on CP‐induced toxicity and the mitochondrial apoptotic pathway in hepatocytes. Animals received a single toxic dose of CP (7.5 mg/kg body weight) with or without combined multiple doses of epigallocatechin gallate (EGCG) and coenzyme Q10 (CoQ10) (15 and 5 mg/kg body weight, respectively). CP‐treated animals showed altered biochemical parameters, denoting hepatotoxicity, which was markedly improved by the multidose treatment with EGCG + CoQ10. The increased levels of oxidants found in the cytosolic and mitochondrial fractions isolated from the liver of CP‐administered rats were significantly attenuated by the combinatorial doses of antioxidants. EGCG + CoQ10 ameliorated the CP‐induced compromised antioxidant defenses, oxidative modification of macromolecules, decreased activities of respiratory chain enzymes, altered membrane depolarization, and swelling of liver mitochondria. Furthermore, EGCG + CoQ10 treatment inhibited CP‐induced apoptosis by suppressing the activation and mitochondrial accumulation of proapoptotic proteins and preventing the inhibition of antiapoptotic protein expression, cytochrome c efflux, caspase‐3 activation, and DNA fragmentation. Histological findings further confirmed the protective effects of EGCG + CoQ10 against CP‐induced cellular injury. Our findings revealed that the combination of EGCG and CoQ10, owing to their individual antioxidant properties, can be an effective remedy, which by maintaining redox hemostasis attenuate the mitochondrial stress‐mediated molecular and cellular processes involved in CP‐induced liver toxicity and cell death.